2019
DOI: 10.3758/s13415-019-00751-x
|View full text |Cite|
|
Sign up to set email alerts
|

High sensation seeking is associated with behavioral and neural insensitivity to increased negative outcomes during decision-making under uncertainty

Abstract: High-level sensation seeking (HSS) has been linked to a range of risky and unhealthy behavior; however, the neural mechanisms underlying such linkage remain unclear. In the present study, we used event-related potential (ERP) with a Balloon Analogue Risk Task (BART) to investigate how sensation seeking modulates brain responses to sequential decision-making with variable reward/loss outcome magnitudes. Behavior data showed that decision-making behavior was significantly affected by the large compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 80 publications
3
12
0
Order By: Relevance
“…It is suggested that high sensation seekers and people lacking premeditation are likely to make disadvantageous decisions in a task with involved risk [ 11 , 15 ]. These findings support previous studies that claim a significant relationship between sensation-seeking, premeditation, and decision-making [ 12 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It is suggested that high sensation seekers and people lacking premeditation are likely to make disadvantageous decisions in a task with involved risk [ 11 , 15 ]. These findings support previous studies that claim a significant relationship between sensation-seeking, premeditation, and decision-making [ 12 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…For mediation and moderation analysis, it was hypothesized that sensation-seeking and lack of premeditation would predict the payoff (Hypothesis 1), and the mood (positive or PLOS ONE make disadvantageous decisions in a task with involved risk [11,15]. These findings support previous studies that claim a significant relationship between sensation-seeking, premeditation, and decision-making [12,14,15]. The second hypothesis is partially fulfilled, where positive mood before IGT performance significantly negatively mediated the direct relationship between both the predictors and payoff (except 26-34 years old men with sensation seeking as a mediator).…”
Section: Plos Onesupporting
confidence: 76%
See 2 more Smart Citations
“…SS is closely related to RS based on reward and novelty seeking [2,13,14]. Higher SS could be oppositely related to RS, as only a higher element of risk could reach the threshold of the seekers' presumed excitement and arousal for reward.…”
Section: Resultsmentioning
confidence: 99%